Multicenter, International Study of MIC/MEC Distributions for Definition of Epidemiological Cutoff Values for Sporothrix Species Identified by Molecular Methods - Espinel Ingroff, A.; Abreu, D. P. B.; Almeida Paes, R.; Brilhante, R. S. N.; Chakrabarti, A.; Chowdhary, A.; Hagen, F.; Córdoba, S.; González González, Gloria María; Govender, N. P.; Guarro, Josep; Johnson, E. M.; et al. (American Society for Microbiology, 2017)
ABSTRACT Clinical and Laboratory Standards Institute (CLSI) conditions for testing the susceptibilities of pathogenic Sporothrix species to antifungal agents are based on a collaborative study that evaluated ﬁve clinically relevant isolates of Sporothrix schenckii sensu lato and some antifungal agents. With the advent of molecular identiﬁcation, there are two basic needs: to conﬁrm the suitability of these testing conditions for all agents and Sporothrix species and to establish species-speciﬁc epidemiologic cutoff values (ECVs) or breakpoints (BPs) for the species. We collected available CLSI MICs/minimal effective concentrations (MECs) of amphotericin B, ﬁve triazoles, terbinaﬁne, ﬂucytosine, and caspofungin for 301 Sporothrix schenckii sensu stricto, 486 S. brasiliensis, 75S. globosa, and 13 S. mexicana molecularly identiﬁed isolates. Data were obtained in 17 independent laboratories (Australia, Europe, India, South Africa, and South and North America) using conidial inoculum suspensions and 48 to 72 h of incubation at 35°C. Sufﬁcient and suitable data (modal MICs within 2-fold concentrations) allowed the proposal of the following ECVs for S. schenckii and S. brasiliensis, respectively: amphotericin B, 4 and 4 g/ml; itraconazole, 2 and 2 g/ml; posaconazole, 2 and 2 g/ml; and voriconazole, 64 and 32 g/ml. Ketoconazole and terbinaﬁne ECVs for S. brasiliensis were 2 and 0.12 g/ml, respectively. Insufﬁcient or unsuitable data precluded the calculation of ketoconazole and terbinaﬁne (or any other antifungal agent) ECVs for S. schenckii, as well as ECVs for S. globosa and S. mexicana. These ECVs could aid the clinician in identifying potentially resistant isolates (non-wild type) less likely to respond to therapy.